Tingkat Kepuasan Pasien terhadap Pelayanan Kefarmasian di Puskesmas Pahandut Kota Palangka Raya: Level of Patient Satisfaction on Pharmaceutical Services in Community Health Centers of Pahandut Palangka Raya - Nurul Chusna; Titra Fetriana; Rabiatul Adawiyah (Borneo Journal of Pharmacy, 2018)
This study aims to determine the level of patient satisfaction with pharmaceutical services at the Pahandut Palangka Raya Community Health Center. This research method is descriptive. The sample in this study were 94 respondents, namely outpatients who received pharmacy services at the Pahandut Palangka Raya Community Health Center. The sampling technique in this study used a purposive sampling technique. The results of the study of patient satisfaction with pharmaceutical services based on the type of service obtained a score of 208 data located in the "very satisfied" area on the type of pharmacy staff responsiveness to patients, in the type of hospitality services pharmacy staff obtained a score of 206 data located "very satisfied", the types of clarity of pharmacy services in providing drug information obtained a score of 212 data located in "very satisfied" areas, in the type of drug service speed the score data 199 were found in "very satisfied" areas, in the types of medical services and medical devices the score data was obtained 200 lies in the "very satisfied" area, in the type of waiting room comfort service the 198 score data is located in the "very satisfied" area, and on the type of service the availability of brochures, leaflets, posters, as well as drug/health information is obtained score data 206 lies in the "very satisfied" area. The results of this study indicate that most patients were very satisfied with the pharmaceutical services provided by the Pahandut Community Health Center in Palangka Raya City.